Global innovation strategies of German hidden champions in key emerging markets - Stephan Buse; Rajnish Tiwari (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2014)
Aim of this study is to analyse product-related innovation strategies of German Hidden Champions (globally leading, mid-sized companies) in the BRIC countries, especially in the fast growing and still unsaturated markets of China and India. With the help of an empirical survey we discover that the BRIC markets are perceived to be of high and growing strategic importance. An overwhelming majority of the surveyed firms market their global, adapted, or exclusively developed products in those countries. The survey reveals that companies very often target high-end, premium segments with global products developed at the headquarters. With such a strong focus on affluent customers Hidden Champions run the risk of ignoring very large customers groups that seek affordable excellence in products (frugal innovation).
urn:nbn:de:gbv:830-tubdok-12764
Keywords: 330; Global Innovation Management; Internationalization of R&D; Innovation Strategy; R&D-Strategy; Hidden Champions